2020
DOI: 10.1108/jsfe-02-2020-0007
|View full text |Cite
|
Sign up to set email alerts
|

Residual properties of normal-strength concrete subjected to fire and sustained elevated temperatures: A comparative study

Abstract: Purpose Concrete is a widely used construction material which can be prepared using locally available resources (aggregates, cement and water) by following relevant standard guidelines. The residual properties of concrete determined by heating in an electric furnace may not produce a similar effect of fire. The purpose of this paper is to compare the effect of a fire with that coming from the exposure of normal strength concrete to predetermined reference temperatures, for which two sets of specimens were heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 29 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…In order to compare the effect of fire with that of exposure of normal strength concrete to predetermined temperatures. Suresh and Sachin (2020) [25] observed that specimens exposed to fire had lower residual compressive and tensile strength and higher porosity than specimens heated in an electric furnace at the same temperature. Mathews et al (2021) [26] carried out an experimental study to observe the effect of elevated temperature on the durability characteristics of ordinary concrete.…”
Section: Introductionmentioning
confidence: 99%
“…In order to compare the effect of fire with that of exposure of normal strength concrete to predetermined temperatures. Suresh and Sachin (2020) [25] observed that specimens exposed to fire had lower residual compressive and tensile strength and higher porosity than specimens heated in an electric furnace at the same temperature. Mathews et al (2021) [26] carried out an experimental study to observe the effect of elevated temperature on the durability characteristics of ordinary concrete.…”
Section: Introductionmentioning
confidence: 99%